The effect of aeration and irrigation on the improvement of soil environment and yield in dryland maize - Yu, Zhen-zhen; Wang, Hong-xuan; Yu, De-shui; Yin, Ning-xia; Zhang, Jing (Frontiers in Plant Science, 2024)
To study the effect of long-term aerated seepage irrigation technology on soil fertility changes and maize yield under continuous maize cropping system in red loam soil, and explaining the mechanism of maize yield increase under this technology, which can provide theoretical basis for crop quality improvement and yield increase under aerated irrigation technology. Therefore, this research was conducted for four field seasons in 2020-2023 at National Soil Quality Observation Experimental Station, Zhanjiang, China. Soil aeration, soil fertility, root growth, physiological traits, and yield indicators were evaluated by conventional underground drip irrigation (CK) and AI. Our results showed that AI treatment significantly improved soil aeration and soil fertility. Increases in soil oxygen content, soil respiration rate, soil bacterial biomass, and soil urease activity were observed, corresponding to increases from 3.08% to 21.34%, 1.90% to 24.71%, 26.37% to 0.09%, and 12.35% to 100.96%, respectively. The effect of aerated irrigation on maize indicators increased year by year. Based on improvements in soil aeration and fertility, root length, root surface area, and root dry weight under AI treatment were enhanced by 15.56%~53.79%, 30.13%~62.31%, and 19.23~35.64% (P<0.05) compared to the CK group. In addition, maize agronomic traits and physiological characteristics showed improved performance, especially over 1.16% to 14.42% increases were identified in maize yield by AI treatment. Further analysis using a structural equation model (SEM) demonstrated that the aerated irrigation technology significantly promotes the improvement of root indicators by enhancing soil aeration and soil fertility. As a result, maize yield could be increased significantly and indirectly.